Prosocial Involvement as a Positive Youth Development Construct: A Conceptual Review - Ching Man Lam (The Scientific World Journal)
This paper discusses the concept of prosocial involvement as a positive youth development construct. How prosocial involvement is defined and how the different theories conceptualize prosocial involvement are reviewed. Antecedents of prosocial involvement such as biological traits, personality, cognitive and emotional processes, socialization experience, culture, and their social context are examined. The relationship between prosocial involvement and adolescent developmental outcomes, together with strategies to promote prosocial involvement in adolescents, are discussed. Finally, directions for future research and practice are proposed.